If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = (m + -1) Reorder the terms: -5 = (-1 + m) Remove parenthesis around (-1 + m) -5 = -1 + m Solving -5 = -1 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -5 + -1m = -1 + m + -1m Combine like terms: m + -1m = 0 -5 + -1m = -1 + 0 -5 + -1m = -1 Add '5' to each side of the equation. -5 + 5 + -1m = -1 + 5 Combine like terms: -5 + 5 = 0 0 + -1m = -1 + 5 -1m = -1 + 5 Combine like terms: -1 + 5 = 4 -1m = 4 Divide each side by '-1'. m = -4 Simplifying m = -4
| 2(x-1)+2(x-2)=10 | | 6(x+1)+4=7x+1 | | f(x)=5x^4+2x | | 4(3s+20)=80 | | y=ln(1.07) | | 500x+24=60 | | -5+10y=x | | X^2+6x-90=8 | | 2log(2x)=7 | | 2=-18+4x | | Logx+2=4 | | x(x^2+16+64)=9(x+8) | | 0.25x+1.5=7.5 | | 3x^4-8=56 | | 6p^2-11=0 | | 26/30x24000 | | -6(5-2x)=q | | 4/10-x)=25-x | | 2P^2-20P+32=0 | | x^(5/4) | | 3y+7x=42 | | x^5/4 | | 10=3r+7r | | X+240y=186 | | 3a-1.2=4 | | 4x+160y=224 | | X+3(x-1)=8-4(2x+3) | | 4(10-x)=25-x | | 25k^2+40k-20=0 | | A=90(n-5) | | 2(3a-1)=2(a+1) | | X+240y=106 |